(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Diagnosis of breast pathology is very important for the management of the patients. Objective: The purpose of the present study was to compare the fine needle aspiration cytology (FNAC) and trucut biopsy for the diagnosis of breast pathology. Methodology: This analytical cross-sectional study was conducted in the Department of Surgery at Bangabandhu Shiekh Mujib Medical University, Dhaka, Bangladesh from 1 April to 31 October 2020 for a period of six months. All the women who were attended at the OPD of the Department of Surgery with the different complaints of breast at any age were selected as study population. The different disease profiles were recorded in the data sheet. Result: A total number of 200 patients were recruited for this study. The mean age with standard deviation was 33.85±7.969 years. The male and female ratio was 1:19. Breast pathology was found in equal in left and right side which was 100(50.0%) cases in each. The central zone was the most common area which was 90(45.0%) cases. Most of the breast pathology was firm which was 170(85.0%) cases. The comparison of FNAC and tru-cut biopsy was done. Fibroadenoma was found in 50(100.0%) cases in FNAC; but in tru-cut biopsy 10(20.0%) case was fibroadenoma; invasive ductal carcinoma was in 30(60.0%) cases and the rest of 10(20.0%) case was Phylloides tumor. In FNAC 1 case was diagnosed as gynaecomatia which was diagnosed as intradermal papilloma in tru-cut biopsy. The difference between the FNAC and tru-cut biopsy for the detection of different pathology of breast was statistically significant (p=0.000). Conclusion: In conclusion there is a significant difference between FNAC and tru-cut biopsy for the detection of breast pathology. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 33-37